Can mindfulness play a role in building social-emotional capacities among youth exposed to screens? - Kim, Soyeon; Munten, Stephanie; Stafford, Shavon; Kolla, Nathan J. (Frontiers in Psychiatry, 2023)
Introduction: Increased screen time coupled with public safety restrictions may pose a serious challenge to adequate social-emotional development in youth during the pandemic. Social-emotional competence (resilience, self-esteem, and self-compassion) are essential for youth to adapt to the “new normal” in the prolonged pandemic timeline. The current study investigated the efficacy of a mindfulness-based intervention on youth social-emotional capacity while accounting for screen time. Methods: 117 community youth participated in a 12-week, online mindfulness-based program and completed pre-, post- and follow-up surveys across five cohorts during the COVID-19 pandemic (spring 2021 to spring 2022). Changes in youths' resilience (RS), self-esteem (SE), and self-compassion (SC) between the three-time points were examined using linear regression analyses (unadjusted, partially adjusted for screen time, and fully adjusted for demographic and screen time variables). The regression models accounted for demographic (age, sex), baseline mental health status, and screen time (passive, social media, video games, and educational types of screen-based behaviours) factors. Results: In an unadjusted regression model, resilience [β= 3.68, 95%CI=1.78-5.50, p<.001], self-compassion [β= 0.50, 95%CI=0.34-0.66, p<.001], and self-esteem [β= 2.16, 95%CI=0.98-3.34, p<.001] significantly increased after the mindfulness program, and the effects were maintained in the follow-up. The efficacy of the mindfulness program persisted after controlling for five types of screen time [RS: β=2.73, 95%CI=0.89-4.57, p<.01; SC: β= 0.50, 95%CI=0.32-0.67, p<.001; SE: β=1.46, 95%CI=0.34-2.59, p<.01] and in a fully adjusted model which additionally accounted for the baseline mental health status and demographic factors [RS: β=3.01, 95%CI=1.20, p<.01; SC: β= 0.51, 95%CI=0.33-0.68, p<.001; SE: β=1.64, 95%CI=0.51-2.77, p<.01] and maintained its impact in the follow-up. Discussion: Our findings reinforce the evidence base on the efficacy of mindfulness and support the use of online mindfulness programs in building social-emotional competencies (i.e., self-compassion, self-esteem, and resilience) among youth exposed to screens during the pandemic.